2015
DOI: 10.14573/altex.1407071
|View full text |Cite
|
Sign up to set email alerts
|

Safety testing of veterinary vaccines using magnetic resonance imaging in pigs

Abstract: SummarySafety testing of veterinary vaccines requires the use of a large number of animals to investigate possible local and systemic reactions. This includes, among others, the pathological examination of the injection site in frequent intervals. This examination requires a selected killing of animals in frequent intervals. To reduce the number of animals needed for this kind of safety testing, magnetic resonance imaging (MRI) was used to detect and quantify possible local reactions after vaccination in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…46 Animals have been bred, used and killed for the purpose of investigating various pathological processes, as well as developing and testing drugs and therapies. 47,48 Glaucoma models, for example, have been established by experimentally inducing ocular hypertension, optic nerve crush or by injecting toxic agents resulting in ganglion cell death. [49][50][51][52][53] Retinal ischaemia is also regularly induced in animals for research purposes.…”
Section: Retinal Organ Culture Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 Animals have been bred, used and killed for the purpose of investigating various pathological processes, as well as developing and testing drugs and therapies. 47,48 Glaucoma models, for example, have been established by experimentally inducing ocular hypertension, optic nerve crush or by injecting toxic agents resulting in ganglion cell death. [49][50][51][52][53] Retinal ischaemia is also regularly induced in animals for research purposes.…”
Section: Retinal Organ Culture Modelsmentioning
confidence: 99%
“…As porcine eyes are a by-product of the food industry, no animals have to be killed solely for research purposes. 48 An assessment of the survival of adult porcine neurosensory retinas was carried out by using 3-day retinal-RPE/ choroid co-cultures. 39 During research studies on RGCs, ex vivo cultures have been shown to remain viable for 7-10 days, which has facilitated the study of molecular mechanisms involved in disease.…”
Section: Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation
“…2007: ASC 3DDR-BN#07032 (FDA approved)) was used, in order to measure the local reaction. The volumes of regions with increased signal intensity at the vaccination side (VS) and at the control side (CS) were bordered semiautomatically at defined signal intensities on a grey scale level from 0 (black) -4096 (white) (Bernau et al, 2015). A region of interest (ROI) was created to cover the largest extent of the area with increased signal intensity at the VS.…”
Section: Mr Image Evaluationmentioning
confidence: 99%
“…Concerning muscle tissue, various alterations resulting from trauma, infection, inflammation or edema can be detected using MRI (Lovitt et al, 2006;May et al, 2000;Schrank et al, 2005;Shellock et al, 1996;Pathria and Boutin, 2009) due to signal intensity changes, especially when performing different protocols (T1-and T2-weightenings; see Hodgson, 2010;Pipe, 1999). Local reactions can be detected via MRI (Brewer et al, 2014;Rudin, 1994;Rudin et al, 1995) and results of our own study in pigs (Bernau et al, 2015) showed that MRI allows the documentation of local reactions after vaccination in the live pig, scanned repeatedly over 29 days.…”
Section: Introductionmentioning
confidence: 99%